Organizational commitment and the well-being of temporary agency workers: A longitudinal study - Galais, Nathalie; Moser, Klaus (Human Relations, 2009)
Previous research found that organizational commitment is positively related to employee well-being. However, in the current age of contingent work, transitions, and `protean careers', the advisability of commitment is questionable. Therefore, we analyzed the role of organizational commitment in one paradigmatic area of contingent work arrangements: temporary agency work. In contrast to standard workers, temporary agency workers have to deal with two organizations: the temporary agency and client organization. Results revealed an ambivalent role of organizational commitment for temporary workers. Cross-sectional commitment towards the client organization had positive effects on workers' well-being, whereas commitment towards the agency had no effects. However, longitudinal analyses revealed that commitment to the client was detrimental to workers' well-being when they experienced reassignment to another client. In sum, we found beneficial and dysfunctional effects of organizational commitment on well-being, which suggest the reconsideration of the role of organizational commitment for individuals in unstable work arrangements.
WiSo-Import:2015-03-26:406
Keywords: Transformation